Effects of neck muscle vibration on subjective visual vertical in an altered visual frame of reference - Christopher A Malaya; Charles S Layne (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2020)
Rod and Frame Testing (RFT) has been used to investigate the effects of an altered visual frame of reference on subjective visual vertical. RFT requires an individual to align a luminous rod as best they can with true vertical. Their vision, however, is restricted by a rotatable square frame. Muscle vibration has effects on proprioceptive integration and appears to provide the illusion of muscle lengthening. This illusion leads not only to reflexive contractions of the stimulated muscle, but reflexive inhibition of its antagonist. We were interested in examining how the head orientation and perception illusions generated by ventral neck vibration would affect a participant's subjective sense of vertical in an altered visual frame of reference. A sample of 21 healthy individuals between the ages of 18 and 35 undertook RFT with concurrent, unilateral vibration over their sternocleidomastoid muscles. We found that RFT significantly influenced our participants even though their heads were stabilized in a chinrest, with or without vibration. Vibration alone was not significantly different from baseline. We believe this indicates the influence of the close visual frame of the RFT is independent of, or even primary over, relevant somatosensory information as it relates to subjective visual vertical.